2014
DOI: 10.1016/j.ijpp.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Discernment of mortality risk associated with childbirth in archaeologically derived forager skeletons

Abstract: An obstetric dilemma may have been a persistent characteristic of human evolution, in which the bipedal female's pelvis is barely large enough to accommodate the birth of a large-brained neonate. Evidence in the archaeological record for mortality risk associated with childbirth is rare, especially among highly mobile, immediate return hunter-gatherer populations. This research explores the idea that if excess mortality is associated with first pregnancy, females will outnumber males among young adult skeleton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 57 publications
3
24
0
Order By: Relevance
“…Although it is generally assumed that dry bone measurements are directly comparable with these references, a cadaver study by Schroeder, Schmidtke, and Bidez () suggests that this can lead to errors for some—though not all—measurements. A number of recent studies (e.g., Kurki, ; Pfeiffer et al, ; Wells et al, ) have also pointed out that pelvic measurements in archaeological samples should not be studied in a vacuum. It is important to consider factors including overall body size and the likely size of neonates in the populations in question.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is generally assumed that dry bone measurements are directly comparable with these references, a cadaver study by Schroeder, Schmidtke, and Bidez () suggests that this can lead to errors for some—though not all—measurements. A number of recent studies (e.g., Kurki, ; Pfeiffer et al, ; Wells et al, ) have also pointed out that pelvic measurements in archaeological samples should not be studied in a vacuum. It is important to consider factors including overall body size and the likely size of neonates in the populations in question.…”
Section: Resultsmentioning
confidence: 99%
“…By modern western standards, the average number of pregnancies per woman may often have been higher in ancient periods, which could have significantly affected female mortality (Roberts & Manchester, ). Bioarchaeological investigations suggest that ancient childbirth morbidity and mortality varied in response to personal factors such as age and body build as well as cultural factors such as mode of subsistence (e.g., McGovern, ; Pfeiffer et al, ; Wells, DeSilva, & Stock, ). This makes death in childbirth important to investigate, not only to gain insight into individual lives in the past but also to improve our understanding of the impact of broad cultural processes and transitions on women's health.…”
Section: Introductionmentioning
confidence: 99%
“…Kurki () has demonstrated that despite narrower bi‐iliac breadth than other global populations, LSA women had relatively large pelvic mid‐planes and outlet canal planes. This implies adaptive allometric remodeling, through selective pressures (Kurki, ; Pfeiffer et al, ). Indeed, there is evidence for excess mortality among very young adult women throughout most of the GCFR (Pfeiffer et al, ).…”
Section: The Archeological Contextmentioning
confidence: 99%
“…This implies adaptive allometric remodeling, through selective pressures (Kurki, ; Pfeiffer et al, ). Indeed, there is evidence for excess mortality among very young adult women throughout most of the GCFR (Pfeiffer et al, ).…”
Section: The Archeological Contextmentioning
confidence: 99%
“…While fetal bones can be recovered when remains are well preserved, burials of pregnant women with the fetus in situ are rarer than one would expect, and there are many cultural practices that may render deaths during pregnancy invisible (Lewis, 2007). Detailed study of sex ratios among young adults may provide a way out of this dilemma by focusing on mortality related to the first pregnancy (Pfeiffer et al, 2014). Detailed study of sex ratios among young adults may provide a way out of this dilemma by focusing on mortality related to the first pregnancy (Pfeiffer et al, 2014).…”
Section: Bioarchaeologymentioning
confidence: 99%